Public views towards community health and hospital-based outpatient services and their utilisation in Zhejiang, China: a mixed methods study. Issue 11 (3rd November 2017) - Wu, Dan; Lam, Tai Pong; Lam, Kwok Fai; Zhou, Xu Dong; Sun, Kai Sing
Abstract : Objective: China is engaged in promoting community health services (CHS) nationwide. This study examines the public's views towards CHS and their utilisation of community-based and hospital-based outpatient services. Design: A mixed methods study using qualitative interviews and a cross-sectional survey. Study setting and participants: The study was conducted among the public between September 2014 and September 2015 in Zhejiang province, China. Six focus groups and 13 individuals were interviewed. The questionnaire was completed by 1248 respondents (response rate: 83%). Primary outcome measures: Utilisation of community-based and hospital-based outpatient services. Results: Functions of CHS perceived by the public included provision of minor illness management, coordination, drug dispensing, follow-up care and patient education. However, many also showed a distrust in primary care providers' (PCPs) competence for confirming the initial diagnosis and management plan. As coordinators, PCPs' integrity was challenged, and PCPs were thought to be potential 'tuo er' (cunning agents who tried to lead patients to some notorious hospitals to make money). Survey results showed that 800 (64.1%) respondents visited hospital-based clinics and 688 (55.1%) visited CHS at least once in the past year. Compared with the uninsured group, those covered by Urban Resident Medical Insurance (adjusted OR (AOR)=1.95, 95% CI 1.24 to 3.07) and Urban Employee Medical Insurance (AOR=2.59, 95% CI 1.59 to 4.24) were more likely to use hospital-based services. Respondents who had a chronic condition were more likely than their counterparts to use both hospital-based services (AOR=1.72, 95% CI 1.18 to 2.49) and CHS (AOR=1.66, 95% CI 1.19 to 2.32). Income levels were positively associated with the likelihood of visiting hospital-based clinics (AOR=1.67, 95% CI 1.15 to 2.42) but negatively associated with the likelihood of using CHS (AOR=0.68, 95% CI 0.48 to 0.96). Conclusions: Demand of hospital-based outpatient services is much higher than the community-based outpatient services. Policy reformers need to take further actions to address the public distrust in PCPs to facilitate their gatekeeping role.